A Single Photon Counting Detector Based on One-Dimensional Vernier Anode - 杨颢 赵宝升 盛立志 李梅 鄢秋荣 刘永安 (Chinese physics letters, 2010)
The mathematical expression on decoding the one-dimensional （1D） Vernier anode is deduced theoretically, and the corresponding 1D-Vernier anode collector is developed. A photon counting imaging and detection system is constructed based on a 1D-Vernier anode detector and electronic readout subsystem. With wavelengths of 253.7nm from the mercury lamp as the ultraviolet emission source, the spatial resolution of the prototype is proved to be better than 100 μm along the x-direction in experiment.